Penyelesaian Sengketa Sertipikat Elektronik Akibat Kesalahan Data Digital Melalui Mekanisme Administratif - Tri Mulyani; Dyah Ayu Sulistyarini; Fayeza Nafesyah Yusuf; Carolina Da Cruz (JURNAL PENELITIAN SERAMBI HUKUM, 2026)
The purpose of this study is to analyze the resolving electronic certificate disputes due to digital data errors through administrative channels. The research method used is normative legal research with a statutory and conceptual approach. The legal materials used consist of laws and regulations, legal literature, and other legal materials related to land administration and administrative dispute resolution. The results of the study indicate that the policy for issuing electronic land certificates based on positive law in Indonesia is regulated by Regulation of the Minister of Agrarian Affairs and Spatial Planning/Head of the National Land Agency of the RI Number 1 of 2021 concerning Electronic Certificates. The stages of the procedure for issuing electronic land certificates include: application submission, document verification, measurement and mapping, certificate issuance, storage and management of electronic certificates. The resolution of disputes arising from digital data errors in Electronic Certificates in principle prioritizes administrative correction mechanisms by authorized officials before resorting to litigation. This aligns with the provisions of Regulation of the Minister of Agrarian Affairs and Spatial Planning/Head of the National Land Agency Number 3 of 2023 concerning the Issuance of Electronic Documents in Land Registration Activities, which places electronic data in the Ministry's Database as a legitimate and authentic data source. Electronic documents issued through the Electronic System contain valid rights holder, physical, and legal data, and all of this data is stored in the electronic database of the Ministry of Agrarian Affairs and Spatial Planning/National Land Agency.